The Economic Impacts of Humpback Whale Depredation on Hatchery‐Released Juvenile Pacific Salmon in Southeast Alaska. Issue 1 (11th February 2019) - Chenoweth, Ellen M.; Criddle, Keith R.
Abstract: The goal of this study was to determine whether humpback whale Megaptera novaeangliae depredation on hatchery‐released juvenile salmon is affecting the economic productivity of hatcheries in Southeast Alaska. From 2010 to 2015, observers monitored five release sites in Chatham Strait, Alaska. Humpback whales were present at the release of 23 of 54 salmon cohorts (defined by release year, species, site, and release strategy). A linear regression model was used to determine whether humpback whale presence at a cohort release affected the proportion of that cohort that survived to harvest. The model included covariates related to management and environmental conditions. The lost fishing revenue for each cohort was determined using the model‐predicted marine survival with and without humpback whales and the average commercial value of the adult salmon. Marine survival of Coho Salmon Oncorhynchus kisutch was significantly lower for cohorts with humpback whale depredation, resulting in an estimated US1 million of lost revenue per year (95% confidence interval = 747, 500–1, 205, 000) associated with whale depredation (23% of observed ex‐vessel fishing revenue from these Coho Salmon cohorts). No significant effect was observed for depredation losses to releases of Chum Salmon O. keta or Chinook Salmon O. tshawytscha, which tended to have low marine survival even in years of no observed whale depredation, possibly due to compensatory depredation from other sources. Despite Chum Salmon having the highest rates of whale depredation, there is no evidence to suggest that preventing humpback whale depredation alone would be sufficient to increase marine survival and fishing revenue for that species, although it may be necessary in concert with other measures.